Case Studies - Kehua Trade Co., LTD - Study On The Development Strategy Of Medium And Small-Sized Foreign Trade Enterprises - Fei, Liu Shao (2008)
This paper summarizes the experience and lessons drawn from operation of the company and points out the crux of the problems---the core competitive power hasn't been formed.